The Influence of Digital Marketing and Product Variety on Consumer Buying Interest in Online Shop Moy Stuff Bengkulu City - Povo Satya Afitri; Ida Ayu Made Er Meytha Gayatri; Yesi Indian Ariska (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the effect of digital marketing and product variety on consumer buying interest at the Moy Stuff Shop in Bengkulu City. The analytical methods used include validity test, homepage linear regression, coefficient of determination, hypothesis testing (t test and f test). This type of research is a quantitative descriptive research, which is a research method in research that examines the status of a human group, an object, a system of thought or a class of humans today. The results of the research show that the regression direction is positive with the equation Y = 11.743 + 0.304X1 + 0.438X2 + e. The coefficient of determination of the value of R square is 0.414. This means that X1 (Digital marketing) and X2 (variety of products), affect buying interest (Y) by 41.40% while the remaining 58.6% is influenced by other variables not examined in this study. The results of the F test show that the significance is 0.000 <0.05. Because the significance level is below 0.05, it shows that X1 (Digital marketing) and X2 (variety of products) have a positive and significant influence together on buying interest (Y). Digital marketing has a positive and significant effect on buying interest, product variety has a positive and significant impact on buying interest because the significant value is less than 0.05.